Accretion onto the Magnetically Charged Regular Black Hole. (July 2017) - Azam, M.; Aslam, A.
Abstract : We investigate the accretion process for static spherically symmetric geometry, i.e., magnetically charged regular black hole with isotropic fluid. We obtain generalized expressions for the velocity ( u ( r ) ), speed of sound ( c s 2 ), energy density ( ρ ( r ) ) and accretion rate ( M ˙ ) at the critical point near the regular black hole during the accretion process. We also plot these physical parameters against fixed values of charge, mass and different values of equation of state parameter to study the process of accretion. We find that radial velocity and energy density of the fluid remain positive and negative as well as rate of change of mass is increased and decreased for dust, stiff, quintessence fluid and phantom-like fluid, respectively .